Improved survival of patients with stage III small-cell lung cancer with primary resection: A SEER-based analysis - Jianlong Jia; Lilith Trassl; Fanli Kong; Benteng Deng; Ruonan Liu; Zhengwu Sun; Xiaoyan Lan; Ali Ö. Yildirim; Georgios T. Stathopoulos; Isis E. Fernandez; Andrea C. Schamberger (Translational Oncology, 2024)
Introduction: : Small cell lung cancer (SCLC) is mostly diagnosed in stage III-IV patients and associated with poor prognosis. To date, surgery is no gold-standard treatment for any SCLC stage and evidence is lacking whether it is beneficial. Here we investigate the impact of surgery, with special attention to stage III SCLC patients, sub-stages and treatment combinations. Methods: : The overall survival (OS) and cancer-specific survival (CSS) of 33,198 SCLC patients (SEER database) were analyzed retrospectively, using various statistical analyses, including propensity score matching (PSM), recursive partitioning, and sequential landmark analyses. Results: : Independent of stage, the OS of patients with surgery-including treatments was almost always better than without surgery. This holds true for stage I-II patients, even after PMS analysis (p < 0.017). The same was found for stage IV patients that underwent surgery plus chemotherapy vs. chemotherapy alone (p = 0.013 after PSM). Stage III patients showed a robust improvement in OS and CSS after surgery (OS: 18 vs.13 months) or surgery plus chemotherapy (OS: 20 vs.15 months) as confirmed by well-balanced PSM and sequential landmark analyses of long-term survivors. More detailed analyses using two independent approaches showed prolonged OS in T3–4/N0–1 and T1–2/N2 stage III patients after surgery or surgery plus chemotherapy. Importantly, primary site surgery had a major survival advantage over surgery at regional sites (p < 0.003). Conclusion: : Our study demonstrates that selected patients of all stages, including stage III T3–4/N0–1 and T1–2/N2, can benefit greatly from surgery-including treatments. Thus, surgery should be included into hospital treatment recommendations for specifically selected SCLC patients.Condensed abstractPrimary resection in patients with stage III SCLC needs re-evaluation. Selected patients with stage III SCLC benefit significantly from surgery. Patients with T3–4/N0–1 and T1–2/N2 stage III SCLC should be considered for surgery.